2017
DOI: 10.1007/s00167-017-4740-2
|View full text |Cite
|
Sign up to set email alerts
|

The trochlear isometric point is different in patients with recurrent patellar instability compared to controls: a radiographical study

Abstract: PurposeThe purpose of the study was to investigate the theoretical isometric point based of the curve of the femoral groove and relating it to the origin of the MPFL femoral tunnel on lateral radiograph by comparing a patellar instability cohort with a control cohort.MethodsFrom a Patellar Instability database the radiographs of 40 consecutive patients were analysed to define Schöttle’s point, and the arc of the circle of the trochlear groove. A comparison population of 20 radiographs from comparable patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
(41 reference statements)
0
6
0
Order By: Relevance
“… ∥ References 2 –8, 10 13, 16, 17, 19, 21 23, 25 32, 34 37, 39 58, 61, 62, 66 70, 72 –75, 77 –85, 88 …”
mentioning
confidence: 99%
“… ∥ References 2 –8, 10 13, 16, 17, 19, 21 23, 25 32, 34 37, 39 58, 61, 62, 66 70, 72 –75, 77 –85, 88 …”
mentioning
confidence: 99%
“…First, patients with ACLR rather than a healthy population with no knee injuries were included as the control group. Although this population was previously reported as comparable with patellofemoral instability, 8,9 and ACLR did not damage the femoral medial condyle, the underlying differences might prevent the generalization of our results. Second, the determination of the geometric centers of the osseous landmarks could be influenced by the image quality and understanding of the saddle sulcus.…”
Section: Discussionmentioning
confidence: 55%
“…Concerns have been raised that patients at risk of RPD have anatomically different knees, particularly for the femoral trochlear shapes. 9 , 20 , 39 , 50 Thus, previous laboratory studies 9 , 38 using healthy cadaveric knees would not be fully relied on in routine clinical practice. Patellofemoral kinematics, contact area and pressure, and stability were further reported to be significantly affected by trochlear dysplasia in a simulated in vitro test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in a study of 64 patients with a median age of 24 years old, Koenen et al found that uoroscopy enabled more accurate femoral tunnel positioning; however, this particular study did not include any comparison with the results obtained by other positioning methods [18]. Campos et al emphasise that as far as trochlear dysplasia is concerned, the Schöttle's point is not suitable for a femoral tunnel; their study based on 40 cases indicates that it is better to use a more proximal point in this group of patients, and that taking this approach should improve accuracy in pre-op planning [34].…”
Section: Discussionmentioning
confidence: 99%